2014
DOI: 10.1007/s10661-014-3753-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of the land snail Helix aspersa for monitoring heavy metal soil contamination in Northeast Algeria

Abstract: The objective of this study was to investigate the impact of anthropogenic activities on soil quality using the land snail Helix aspersa as a bioindicator. Soil samples and snails were collected from several sites in Northeast Algeria during the summer and winter of 2010. All of the sites were chosen due to their proximity to industrial factories-a potential source of soil pollution via heavy metal contamination. The concentration of heavy metals (Pb, Cd, Mn, and Fe) in soil samples was analyzed using atomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 44 publications
2
9
2
Order By: Relevance
“…Hence, the increase of GST activity could be due to the pollutants-inducing the activation of the natural antioxidant defense systems (Elia et al, 2007). Our result coincides with that of Larba and Soltani (2014) who reported that GST activity was significantly increased in the digestive gland of the land snails C. aspersus collected from several sites in Northeast Algeria. An activation of GST has been also reported in this species collected from the same sites exposed to metallic pollution (Bairi et al, 2020;Abdel-Halim et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, the increase of GST activity could be due to the pollutants-inducing the activation of the natural antioxidant defense systems (Elia et al, 2007). Our result coincides with that of Larba and Soltani (2014) who reported that GST activity was significantly increased in the digestive gland of the land snails C. aspersus collected from several sites in Northeast Algeria. An activation of GST has been also reported in this species collected from the same sites exposed to metallic pollution (Bairi et al, 2020;Abdel-Halim et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with this result, the decrease in AChE activity was reported in the head of Cantareus aspersus collected from the same north-east Algerian sites compared to snails of the reference site (El Kala). This is likely explained by the metal pollution with high concentrations of Fe, Al2O3, MgO and FeO (Douafer et al, 2020) and Fe, Mn, Pb, and Cd (Larba and Soltani, 2014). Bairi et al (2020) have reported inhibition of AChE activity in C. aspersus collected from the site of El Hadjar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such assessment can avoid a serious impact on the global biodiversity (Ficken and Byrne 2013;Jan et al 2015;Guerriero et al 2018a). Many regions in Algeria have been developed without adequate planning resulting in soils and water reported as being heavily polluted with various metals including mercury (Hg), arsenic (As), lead (Pb), zinc (Zn), manganese (Mn), lithium (Li), cadmium (Cd ) and chromium (Cr) (Tahar and Keltoum 2011;Benhaddya and Hadjel 2014;Larba and Soltani 2014;Boudia et al 2019;Talbi and Kachi 2019). Evidence of different metals also appears in the waters of Medjarda River, an urban river of Souk-Ahras City in Northeastern Algeria.…”
Section: Introductionmentioning
confidence: 99%
“…Boudechiche (2007), focused on helicoidal biodiversity in El-Kala (northeast of Algeria). The research of Larba and Soltani (2014) approached gastropods as bioindicators of the environmental quality in the northeast of Algeria and ultimately, Bouaziz-Yahiatene and Medjdoub-Bensaad' report, in 2016, investigated the diversity of the malacofauna present in the Great Kabylia (north of Algeria). Nevertheless, the regions of Constantine and Oum-El-Bouaghi in northeastern Algeria have been so far a virgin terrain.…”
Section: Introductionmentioning
confidence: 99%